Healthcare transition challenges faced by young adults with autism spectrum disorder. Issue 6 (17th October 2015) - Hall, T; Kriz, D; Duvall, S; Nguyen‐Driver, M; Duffield, T
Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder that impacts communicative interactions, with patterns of repetitive and restricted behaviors, interests, and cognitive rigidity. Recent incidence rate estimates for ASD are 1 in 68, and primarily male (4:1). A major epidemiological issue in ASD is transitioning to independence in adulthood, particularly navigating the healthcare system. This commentary will focus on approaches healthcare providers can use to not overlook and support individuals with ASD.